(untitled) (Comparative Professional Pedagogy, 2021)
The paper is devoted to analysing teachers’ professional standards in Australia and Ukraine to reveal the essence and role of inclusive competence as a significant component of quality teacher professional identity. This study aims to examine and compare current policies and practices in both countries to explain why social justice is such a critical element in preparing qualified teachers and is crucial for enhancing quality teaching. According to the current research, quality teaching for inclusive education in Australia, as in Ukraine, has long been a hotly debated national issue – a subject of concern for politicians, lawmakers, the media, and society. A comparative analysis allows us to compare the Ukrainian and Australian contexts in inclusive education by considering professional teacher standards and policy documents that have impacted quality education. An analysis of Australia’s theoretical and practical achievements in defining the professional competencies and personal characteristics of a quality teacher capable of successful work in an inclusive school setting allowed us to map out favourable ways to enhance teacher training and promote inclusive education in Ukraine. The research results may have broad applicability in improving quality teaching in Ukraine as it reaches global education.